On the performance of code word diversity based quasi orthogonal space time block codes in multiple-input-multiple-output systems - SenthilKumar Kumaraswamy; Palanivelan Manickavel; Noormohammed Valimohamad; Helanvidhya Thankaraj; Yogalakshmi Venkatesan; Bakyalakshmi Veeraragavan (Institute of Advanced Engineering and Science, 2020)
In the recent past, a lot of researches have been put into designing a Multiple-Input-Multiple-Output (MIMO) system to provide multimedia services with higher quality and at higher data rate. On par with these requirements, a novel Quasi Orthogonal Space Time Block Code (QOSTBC) scheme based on code word diversity is proposed, which is a multi-dimensional approach, in this paper. The term code word diversity is coined, since the information symbols were spread across many code words in addition to traditional time and spatial spreading, without increasing transmission power and bandwidth. The receiver with perfect channel state information estimates the transmitted symbols with less probability of error, as more number of samples is available to estimate given number of symbols due to the extra diversity due to code words. The simulation results show a significant improvement in the Bit Error Rate (BER) performance of the proposed scheme when compared with the conventional schemes.